2021
DOI: 10.1093/ajcn/nqaa394
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle after colorectal cancer diagnosis in relation to recurrence and all-cause mortality

Abstract: Background An unhealthy lifestyle is associated with the risk of colorectal cancer (CRC), but it is unclear whether overall lifestyle after a CRC diagnosis is associated with risks of recurrence and mortality. Objectives To examine associations between postdiagnosis lifestyle and changes in lifestyle after a CRC diagnosis with risks of CRC recurrence and all-cause mortality. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 27 publications
1
44
0
Order By: Relevance
“…[ 18 ] Overall lifestyle (including body weight, physical activity, diet, and alcohol intake) after diagnosis was not associated with CRC recurrence, while it was inversely associated with all-cause mortality. [ 89 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 18 ] Overall lifestyle (including body weight, physical activity, diet, and alcohol intake) after diagnosis was not associated with CRC recurrence, while it was inversely associated with all-cause mortality. [ 89 ]…”
Section: Discussionmentioning
confidence: 99%
“…The lower risk of death associated with a higher consumption of fruits and vegetables may be the result of inverse associations with diseases of the circulatory, respiratory and digestive systems [56]. Emerging evidence has shown that lifestyle, including diet, after a Colorectal Cancer (CRC) diagnosis might affect all-cause and CRC-specific mortality risk, in particular, in terms of risk of relapse, mortality [57] and survival [58]. Other studies have highlighted that lifestyle and eating habits are associated with gastric adenocarcinoma [59].…”
Section: Discussionmentioning
confidence: 99%
“…Efforts to quantify overall lifestyle in CRC survivors have been limited to assessing adherence to lifestyle recommendations [ 14 , 23 , 24 ]. Previous studies among CRC survivors showed that an overall healthy lifestyle after CRC diagnosis was associated with improved survival [ 14 , 24 ], but not among long-term survivors [ 23 ]. The results regarding CRC recurrence were inconsistent [ 14 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies among CRC survivors showed that an overall healthy lifestyle after CRC diagnosis was associated with improved survival [ 14 , 24 ], but not among long-term survivors [ 23 ]. The results regarding CRC recurrence were inconsistent [ 14 , 24 ]. Our group reported that post-diagnosis lifestyle might be more important than lifestyle before diagnosis, as the summary lifestyle score before CRC diagnosis was not associated with all-cause mortality [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation